Ag loaded B-doped-g C3N4 nanosheet with efficient properties for photocatalysis. (1st October 2019) - Thorat, Nirmala; Yadav, Asha; Yadav, Manisha; Gupta, Suraj; Varma, Ranjana; Pillai, Saju; Fernandes, Rohan; Patel, Maulik; Patel, Nainesh
Abstract: Three material engineering strategies in the form of doping (Boron-doping), nanostructuring (nanosheet (NS) formation) and decorating with plasmonic nanoparticles (loading with Ag metal), were integrated to improve the photocatalytic activity of graphitic carbon nitride (gC3 N4 ). Concentrations of B-doping and Ag-loading were optimized to maximize the catalytic performance in the final nanocomposite of Ag-loaded B-doped gC3 N4 NS. Combined effect of all three strategies successfully produced over 5 times higher rate towards degradation of organic dye pollutant, when compared to unmodified bulk gC3 N4 . Detailed characterization results revealed that incorporation of B in gC3 N4 matrix reduces the band gap to increase the visible light absorption, while specific surface area is significantly enhanced upon formation of NS. Decoration of Ag nanoparticles (NPs) on B-doped gC3 N4 NS assists in fast transfer of photogenerated electrons from gC3 N4 to Ag NPs owing to the interfacial electric field across the junctions and thus reduces the recombination process. Investigations on individual strategies revealed that decoration of Ag NPs to induce better charge separation, is the most effective route for enhancing the photocatalytic activity. Graphical abstract: Image 1 Highlights: Three material engineering strategies were employed to synthesize Ag loaded B-doped gC3 N4 nanosheet. B incorporation in gC3 N4 extends visible light absorption. Nanosheet formation results in higher exposed surface area. Ag loading prolongs charge carrier lifetime via efficient electron-hole pair separation at the interface. Ag loaded B-gC3 N4 shows 5.2 times higher photocatalytic performance compared to pure gC3 N4 .